Pharmacological Inhibition of Endogenous Hydrogen Sulfide Production Slows Bladder Cancer Progression in an Intravesical Murine Model - Sydney Relouw; George J. Dugbartey; Patrick McLeod; Natasha N. Knier; Francisco Martinez Santiesteban; Paula J. Foster; Heather-Anne C; Nicole M. Hague; Jenna Caine; Kaitlin Belletti; Sally Major; Caroline O'Neil; et al. (MDPI AG, 2024)
Present bladder cancer therapies have relatively limited therapeutic impact and account for one of the highest lifetime treatment costs per patient. Therefore, there is an urgent need to explore novel and optimized treatment strategies. The present study investigated the effects of inhibiting endogenous hydrogen sulfide (H2S) production on bladder cell viability and in vivo tumor progression. We targeted the H2S-producing enzyme, cystathionine <semantics>γ</semantics>-lyase, in 5637 cells using propargylglycine (H2S inhibitor) and performed cytofluorimetric analysis to evaluate cell viability. We then tested the efficacy of propargylglycine alone or in combination with gemcitabine (conventional chemotherapy) in an intravesical murine model of bladder cancer. Magnetic resonance imaging and immunohistochemical staining for cell proliferation, apoptosis, immune-cell infiltration, and neovascularization were performed to evaluate tumor response. Compared to control conditions or cohorts, propargylglycine administration significantly attenuated bladder cancer cell viability in vitro (p < 0.0001) and tumor growth (p < 0.002) and invasion in vivo. Furthermore, propargylglycine enhanced the anti-cancer effects of gemcitabine, resulting in tumor regression (p < 0.0001). Moreover, propargylglycine induced cleaved PARP-1-activated apoptosis (p < 0.05), as well as intratumoral CD8+ T cell (p < 0.05) and F4/80+ macrophage (p < 0.002) infiltration. Propargylglycine also reduced intratumoral neovascularization (p < 0.0001) and cell proliferation (p < 0.0002). Importantly, the pro-apoptotic and anti-neovascularization effects of gemcitabine were enhanced by propargylglycine co-administration. Our findings suggest that inhibition of endogenous H2S production can be protective against bladder cancer by enhancing the chemotherapeutic action of gemcitabine and may be a novel pharmacological target and approach for improved bladder cancer diagnosis and treatments in the future.